Effect of bilateral carotid body resection on the counterregulatory response to hypoglycaemia in humans. Issue 1 (1st January 2015) - Wehrwein, Erica A.; Limberg, Jacqueline K.; Taylor, Jennifer L.; Dube, Simmi; Basu, Ananda; Basu, Rita; Rizza, Robert A.; Curry, Timothy B.; Joyner, Michael J.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Hyperoxia blunts hypoglycaemia counterregulation in healthy adults. We hypothesized that this effect is mediated by the carotid bodies and that: (i) hyperoxia would have no effect on hypoglycaemia counterregulation in carotid body‐resected patients; and (ii) carotid body‐resected patients would exhibit an impaired counterregulatory response to hypoglycaemia. What is the main finding and its importance? Our data indicate that the effect of hyperoxia on hypoglycaemic counterregulation is mediated by the carotid bodies. However, a relatively normal counterregulatory response to hypoglycaemia in carotid body‐resected patients highlights: (i) the potential for long‐term adaptations after carotid body resection; and (ii) the importance of redundant mechanisms in mediating hypoglycaemia counterregulation. Hyperoxia reduces hypoglycaemia counterregulation in healthy adults. We hypothesized that this effect is mediated by the carotid bodies and that: (i) hyperoxia would have no effect on hypoglycaemia counterregulation in patients with bilateral carotid body resection; and (ii) carotid body‐resected patients would exhibit an impaired counterregulatory response to hypoglycaemia. Five patients (three male and two female) with bilateral carotid body resection for glomus tumours underwent two 180 min hyperinsulinaemic, hypoglycaemic (∼3.3 mmol l−1) clamps separated by a minimum of 1 week and randomized to either normoxia (21% fractional inspired O2) or hyperoxia (100% fractional inspired O2). Ten healthy adults (seven male and three female) served as control subjects. Hypoglycaemia counterregulation in carotid body‐resected patients was not significantly altered by hyperoxia (area under the curve expressed as a percentage of the normoxic response: glucose infusion rate, 111 ± 10%; cortisol, 94 ± 6%; glucagon, 107 ± 7%; growth hormone, 92 ± 10%; adrenaline, 89 ± 26%; noradrenaline, 79 ± 15%; main effect of condition, P > 0.05). This is in contrast to previously published results from healthy adults. However, the counterregulatory responses to hypoglycaemia during normoxia were not impaired in carotid body‐resected patients when compared with control subjects (main effect of group, P > 0.05). Our data provide further corroborative evidence that the effect of hyperoxia on hypoglycaemic counterregulation is mediated by the carotid bodies. However, relatively normal counterregulatory responses to hypoglycaemia in carotid body‐resected patients highlight the importance of redundant mechanisms in mediating hypoglycaemia counterregulation.